COORDINATION OF OFFICIAL DEVELOPMENT ASSISTANCE - Morule, Lerumo Cedric Cyphus (My University, 2011)
The National Policy Framework and Guidelines for ODA Management prescribes that Official Development Assistance (ODA) in South Africa is decentralized. The three spheres (national, province and local) of government, described in the Constitution of the Republic of South Africa (1996) as “distinct”, “interdependent” and “interrelated”, with emphasis on cooperative governance, may each solicit ODA. The ODA guidelines and practice in the Department of Provincial and Local Government (dplg) have exposed a gap in effective mechanisms for coordination of ODA in the three spheres. The purpose of the exploratory research described in this research report was to determine from practice, policy and legislative perspectives what the successes or failures of the coordination of ODA were. The dplg was used as a case study, with convenient data gathering from other sector departments’ ODA coordinators also taking place. The main finding of the study is that, despite the presence of the policy and legislative environment governing ODA, ODA coordination remains poor in the three spheres. A model for possible adaptation was recommended to improve coordination
MM - P&DM
Keywords: Official Development Assistance; Co-operative governance; Decentralised governance